Implementasi Kewajiban Mempekerjakan Tenaga Kerja Lokal Pada Perusahaan Pertambangan Batubara Di Kabupaten Berau Kalimantan Timur - Aprilia; Haris Retno Susmiyati; Erna Susanti (Jurnal Risalah Hukum, 2019)
Today's labor competition is a problem, especially in the context of reducing unemployment in the region. Since regional autonomy the issue of labor has become a problem that is the authority of the regional government, so the regional government continues to work hard in overcoming the problem. This socio legal research wants to answer two problems, firstly, how the legal arrangement regarding the obligation to employ local labor force that applies. Secondly, knowing and analyzing the implementation related to the obligation to employ local workers based on the provisions of the Regional Regulation of Berau Regency, East Kalimantan Province. Law Number 4 Year 2009 Concerning Mineral and Coal only regulates the obligation to prioritize the use of local labor, likewise in Law Number 13 Year 2003 regarding Manpower there is no regulation on the obligation to employ local workers. This is different from Berau District Regulation No. 8 of 2018 concerning Protection of Local Workers which regulates the obligation to employ local workers as much as 80% (eighty percent) in the company.